2012
DOI: 10.1002/etc.1913
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic mercury accumulation in rice (Oryza sativa L.)

Abstract: To investigate the source and process of inorganic mercury (IHg) accumulation in rice, we monitored the concentrations of IHg in tissues of rice plants (Oryza sativa L.) from four experimental plantation plots. Biweekly during the rice‐growing season, tissues of rice plants, corresponding soil, precipitation, and irrigation water samples were collected. The sampling data support the following: (1) the atmosphere is the principal source of IHg to the aboveground parts of the rice plant; (2) both the atmosphere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 34 publications
7
37
0
1
Order By: Relevance
“…Besides, recent studies revealed that IHg accumulated in rice grains could be mainly from the atmosphere but not soil (Greger et al, 2005;Lodenius et al, 2003;Mao et al, 2013;Meng et al, 2012), and thus it could be less possible to find any significant relationship between extractable IHg and grain IHg levels. However, it would also be interesting to explore the possibility of using (NH 4 ) 2 S 2 O 3 extraction to predict IHg uptake or bioaccumulation from soils, which may help understand the mechanisms of IHg uptake by rice plants.…”
Section: Extractantmentioning
confidence: 97%
“…Besides, recent studies revealed that IHg accumulated in rice grains could be mainly from the atmosphere but not soil (Greger et al, 2005;Lodenius et al, 2003;Mao et al, 2013;Meng et al, 2012), and thus it could be less possible to find any significant relationship between extractable IHg and grain IHg levels. However, it would also be interesting to explore the possibility of using (NH 4 ) 2 S 2 O 3 extraction to predict IHg uptake or bioaccumulation from soils, which may help understand the mechanisms of IHg uptake by rice plants.…”
Section: Extractantmentioning
confidence: 97%
“…It evidences the complexity of the Hg accumulation process in rice seeds and the influence of several environmental factors. Among the variables that affect such mechanisms there is the rice cultivar (Horvat et al, 2003;Li et al, 2013) and the contribution from atmospheric deposition (Horvat et al, 2003;Meng et al, 2010Meng et al, , 2012Yin et al, 2013a). The latter one principally influenced the top soil (0-10 cm) of rice paddies (Li et al, 2008b), which is evidenced by one order of magnitude decrease of Hg concentration with in 1km distance from the artisanal Hg mining sites (Meng et al, 2011).…”
Section: Hg Concentration and Species Distribution In Paddy Soilmentioning
confidence: 99%
“…A contrasting pattern of uptake and plant distribution of Hg species has been largely documented (Horvat et al, 2003;Meng et al, 2010Meng et al, , 2011Meng et al, , 2012Rothenberg et al, 2011). Soil contribution appears as the main source of iHg in roots .…”
Section: Combination Of Speciation and Hg Isotopic Pattern For The Inmentioning
confidence: 99%
“…MeHg in soil was first absorbed by roots and then translocated to the above-ground parts (leaves and stalk, [9]). However, IHg accumulated in rice plants could mainly come from the atmosphere through leaf uptake, but not from soil [10][11], because the root surface, acting as IHg barrier, could inhibit the translocation of IHg through the root system to the aboveground parts, but could not inhibit MeHg transfer [12]. Meanwhile, recently rice leaves and stalk burial is being encouraged all over the world as an economical and environmentally friendly method to get rid of rice residuals.…”
mentioning
confidence: 99%